Contamination of the internal handles/knobs of public restroom doors with potentially pathogenic bacteria - Na'was, Tarek (2018)
Microorganisms are present on all surfaces, to which they were carried by many direct and indirect methods of transmission. Regular cleansing of any surface, even using good detergents, will not prohibit organisms from reoccupying these surfaces again and in avery brief period of time. This study aimed at detecting the presence of bacteria on the surfaces of the inside handles/knobs of public restroom doors. Samples collected from doors of 16 public toilets (8 for males and 8 for females) were tested for the presence of bacteria. The results showed that almost all the door handles/knobs (93.8%) were contaminated with potentially pathogenic bacteria. The following organisms were isolated: Staphylococcus aureus (68.8%), Citrobacter freundii (25%), Enterobacter cloacae (18.8%), Rahnellaaquatilis (3.3%), Shigella sonnei (3.3%) and Pantoea sp. (3.3%), indicating that the contamination, most probably, was caused by the hands of the toilet users. It was noted that samples from the males’ restrooms were more contaminated than those from the females’ restrooms and that door handles carried more organisms than door knobs. These results should alert public toilets’ users that extreme caution must be executed while using these toilets, as the internal door handles/knobs, may be a potential source of pathogenic bacteria.